Yogurt consumption and risk of accelerated aging: A population-based study from the NHANES 2003–2006 - Yue, Xinghai; Liu, Hongfei; Guo, Wenzhao; Gao, Yuhang; Shi, Shaoshun (Frontiers in Nutrition, 2024)
Introduction Yogurt consumption is beneficial to health, but its association with aging remains unclear. This study aims to explore the relationship between yogurt consumption and aging using data from the 2003–2006 National Health and Nutrition Examination Survey (NHANES). Methods We used data from 4,056 participants to examine the relationship between yogurt consumption and aging. Yogurt consumers were defined as individuals who consumed yogurt at least once per year. Phenotypic age acceleration was used as a surrogate marker for aging. Nearest-neighbor propensity score matching (PSM) was applied to reduce bias, followed by weighted multivariate logistic regression analysis, subgroup analysis, and restricted cubic spline (RCS) to investigate the relationship between yogurt consumption and aging. Results Yogurt consumption was associated with a lower risk of accelerated aging compared to non-consumers (OR = 0.544, 95% CI: 0.354–0.836, p = 0.020). A U-shaped relationship was observed between the frequency of yogurt intake and the risk of accelerated aging. Additionally, yogurt consumption was related to a lower risk of overweight status. Discussion These findings suggest that yogurt consumption may reduce the risk of accelerated aging and may also be linked to a lower risk of overweight status. This could provide a promising avenue for exploring the beneficial effects of dietary factors on lifespan extension.